Encouraging EFL Students’ Willingness to Communicate inside Vietnamese High School Classrooms: Teachers’ Strategies and Students’ Beliefs - Viet Hoang; Hung Bui (Applied Research on English Language, 2023)
Despite a currently proliferating interest in the second language (L2) willingness to communicate (WTC), much less has investigated Asian high school students’ beliefs about L2 teachers’ strategies to encourage WTC inside the classroom. This qualitative study explores the strategies employed by Vietnamese EFL teachers to encourage their students’ WTC inside the classroom and students’ beliefs about their teachers’ strategies. Data were collected from semi-structured interviews with seven teachers and eight students. Results revealed that the teachers employed six main strategy groups, namely grouping, warm-up, topic choice, correction strategies, class atmosphere, and motivational strategies. Also, the students indicated their preferences for some strategies and suggested other strategies which they believed to be effective. They expressed expectations and suggested ways to improve their teachers’ strategies to encourage WTC inside the classroom. The students’ preferences and recommendations of strategies reflected contextual factors. As WTC is a context-sensitive construct, it might be necessary for L2 teachers to understand their students’ beliefs to foster L2 WTC effectively inside the classroom.